2013
DOI: 10.1021/ef401143v
|View full text |Cite
|
Sign up to set email alerts
|

Co-production of Pyrolysis Oil in District Heating Plants: Systems Analysis of Dual Fluidized-Bed Pyrolysis with Sequential Vapor Condensation

Abstract: Flash pyrolysis of biomass yields a liquid applicable as a fuel oil substitute and as a basis for production of chemicals and fuels. Biomass, being a renewable resource, is foreseen to be in increasing demand. An increased usage may lead to scarcity of biomass and emphasizes the need for high-efficiency conversion processes. In this study, the efficiency and capacity aspects of an integration of pyrolysis oil production with a district heating plant by means of dual fluidized-bed technology has been modeled. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 17 publications
(36 reference statements)
1
20
0
Order By: Relevance
“…The production is planned at 50,000 t/y. Gustavsson and Nilsson [7] investigated the integration of a flash pyrolysis reactor including sequential vapour condensation of the pyrolysis oil in a CHP plant and demonstrated that the potential for producing pyrolysis oil is considerable, especially during the summer months. The proposed plant in Ref.…”
Section: Pyrolysismentioning
confidence: 99%
See 4 more Smart Citations
“…The production is planned at 50,000 t/y. Gustavsson and Nilsson [7] investigated the integration of a flash pyrolysis reactor including sequential vapour condensation of the pyrolysis oil in a CHP plant and demonstrated that the potential for producing pyrolysis oil is considerable, especially during the summer months. The proposed plant in Ref.…”
Section: Pyrolysismentioning
confidence: 99%
“…The proposed plant in Ref. [7] uses sequential condensation of the pyrolysis oil at different temperature levels. A part of the condenser heat could not be utilized and was discharged as waste heat.…”
Section: Pyrolysismentioning
confidence: 99%
See 3 more Smart Citations